2016
DOI: 10.1016/j.neuroimage.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Neural activity during sentence processing as reflected in theta, alpha, beta, and gamma oscillations

Abstract: We used magnetoencephalography (MEG) to explore the spatiotemporal dynamics of neural oscillations associated with sentence processing in 102 participants. We quantified changes in oscillatory power as the sentence unfolded, and in response to individual words in the sentence. For words early in a sentence compared to those late in the same sentence, we observed differences in left temporal and frontal areas, and bilateral frontal and right parietal regions for the theta, alpha, and beta frequency bands. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
102
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 67 publications
22
102
2
Order By: Relevance
“…The current study pertains to participants from the MEG session in the auditory modality. A more in depth description of the experimental protocol has been provided elsewhere (Lam, Schoffelen, Udden, Hulten, & Hagoort, 2016;Schoffelen et al, 2017). All participants were right-handed, reported normal hearing, had normal or corrected-to-normal vision, and had no known history of neurological, developmental or language deficits.…”
Section: Participantsmentioning
confidence: 99%
“…The current study pertains to participants from the MEG session in the auditory modality. A more in depth description of the experimental protocol has been provided elsewhere (Lam, Schoffelen, Udden, Hulten, & Hagoort, 2016;Schoffelen et al, 2017). All participants were right-handed, reported normal hearing, had normal or corrected-to-normal vision, and had no known history of neurological, developmental or language deficits.…”
Section: Participantsmentioning
confidence: 99%
“…A GC spectral peak in the gamma frequency range was absent in our data. Although studies in the visual system allow for experimental paradigms eliciting robust and strongly modulated gamma band rhythmicity, language paradigms do not typically lead to similarly strong local gamma-band responses (23), rendering the likelihood of detecting gamma-band interactions low. In addition, characterization of feedforward and feedback connections based on their cytoarchitectonic connectivity profiles is likely to be more distinct in peripheral sensory systems than in higher cortical regions (24), such as the higher-order areas in the human brain network for language.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we found that rhythmic activity in the alpha frequency range (8-12 Hz) propagates from temporal cortical areas to frontal cortical areas, and that beta frequency rhythmic activity (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) propagates in the opposite direction. These results indicate the functional relevance of rhythmic directed interactions during language processing, where interactions between areas are supported by different frequency bands, depending on the direction of the interaction.…”
mentioning
confidence: 94%
“…There is one study that does not fit the more or less clear‐cut picture outlined above. Lam, Schoffelen, Uddén, Hultén, and Hagoort () compared coherent and scrambled sentences (word lists) during reading. They found decreased theta power in bilateral occipitotemporal regions and increased theta in left anterior superior temporal regions for sentences compared to word lists.…”
Section: Syntactic and Semantic Structure Buildingmentioning
confidence: 99%